2015
DOI: 10.1155/2015/752512
|View full text |Cite
|
Sign up to set email alerts
|

Levo‐Tetrahydropalmatine Attenuates Bone Cancer Pain by Inhibiting Microglial Cells Activation

Abstract: Objective. The present study is to investigate the analgesic roles of L-THP in rats with bone cancer pain caused by tumor cell implantation (TCI). Methods. Thermal hyperalgesia and mechanical allodynia were measured at different time points before and after operation. L-THP (20, 40, and 60 mg/kg) were administrated intragastrically at early phase of postoperation (before pain appearance) and later phase of postoperation (after pain appearance), respectively. The concentrations of TNF-α, IL-1β, and IL-18 in spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Clinically, L-THP is traditional Chinese medicine for 40 years and used for the treatment of cardiovascular and a lot of pains [14,15]. Studies have been demonstrated that L-THP shows a protective role in cardio, blood vessels and neural tissues via anti-apoptosis, anti-oxidant and anti-inflammation [16][17][18]. As previously reported, natural alkaloids have also been shown their brilliant anti-cancer activities in some human cancers, such as leukemia and prostate cancer [19,20].…”
Section: Ivyspringmentioning
confidence: 99%
“…Clinically, L-THP is traditional Chinese medicine for 40 years and used for the treatment of cardiovascular and a lot of pains [14,15]. Studies have been demonstrated that L-THP shows a protective role in cardio, blood vessels and neural tissues via anti-apoptosis, anti-oxidant and anti-inflammation [16][17][18]. As previously reported, natural alkaloids have also been shown their brilliant anti-cancer activities in some human cancers, such as leukemia and prostate cancer [19,20].…”
Section: Ivyspringmentioning
confidence: 99%
“… 2 , 25 Microglia exert a function in the spinal cord similar to that of macrophages in the periphery and play an important role in promoting the development of BCP. 6 , 7 , 26 28 It is observed that microglia in resting state are highly dynamic in vivo. They continuously scan their immediate environment and interact with other elements in central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main active ingredients of CYHS, tetrahydropalmatine, also known as fumarate B (dl-THP), 90 prevents hyperlipidemia, 91 attenuates neuronal apoptosis induced by cerebral ischemia-reperfusion injury, 92 offers neuroprotection, 93 has antitumor effects, 94 provides analgesia, 95 prevents memory impairment, 96 and ameliorates the development of anxiety and depression. 97,98 Asparagus cochinchinensis (Lour.)…”
Section: Polygala Tenuifolia Willdmentioning
confidence: 99%